Political Information for Young Women - Reny Yunia Ningtias; Candrasari, Yuli (HM Publisher, 2023)
Patriarchal culture is inherent in Indonesia, where women are weak, do not have the right to vote, and are always subordinate to men, so political information is still considered taboo by women. This study aimed to examine the preferences of young women regarding political information in the media. This study uses qualitative research methods with data collection techniques using in-depth interviews and literature studies. The informants in this study were 16-year-old Surabaya female adolescents. The results of this study indicate that young women in Surabaya are not anti-political and do not want to accept politics, but political information for young women is less interesting than other information.